A study of the epidemiology and socio-economic impact of anthrax in Luangwa Valley in Zambia - Meltzer, David George Anton (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2003.